Comparison of three S‐β‐CDs with different degrees of substitution for the chiral separation of 12 drugs in capillary electrophoresis. Issue 9 (11th July 2017) - Wang, Zhaokun; Zhang, Qiongwen; Luo, Linda; Sun, Tiemin; Guo, Xingjie
Abstract: Three kinds of sulfated β‐cyclodextrin (S‐β‐CD), including a single isomer, heptakis‐6‐sulfato‐β‐cyclodextrin (HS‐β‐CD), degree of substitution (DS) of 7, which was synthesized in our laboratory and another two commercialized randomly substituted mixtures, a sulfated β‐cyclodextrin with DS of 7 to 11, as well as a highly sulfated‐β‐cyclodextrin with DS of 12 to 15, were used for the enantioresolution of 12 drugs (the β‐blockers, phenethylamines, and anticholinergic agents) in capillary electrophoresis. The enantioseparation under varying concentrations of S‐β‐CD and background electrolyte pH were systematically investigated and compared. Based on the experimental results, the effect of the nature of S‐β‐CD and analyte structure on the enantioseparation is discussed. Abstract : Basic analyte is positively charged at low BGE pH. Sulfated β‐cyclodextrin is anionic over the entire pH range, which can thereby lead to ionic interaction between the host and guest in addition to the hydrophobic inclusion. The formed inclusion complex migrates towards the anode itself, which is opposite to the direction of EOF. Which polarity the analyte can detect is determined by both EOF and chiral selector.